LEADING THROUGH CHANGE: HOW ADAPTIVE PRINCIPALS SHAPE POSITIVE SCHOOL CULTURE AND CLIMATE - Sofi Ali; Lisa Virdinarti Putra (Universitas Islam Negeri Mataram, 2026)
Educational institutions must navigate rapid change and increasing complexity, making school leadership a crucial factor in shaping organizational conditions. This study investigates the relationship between principals’ adaptive leadership and two organizational outcomes: positive school culture and school climate. Using a quantitative explanatory design, data were collected from 63 vocational high school teachers through self-administered questionnaires. Adaptive leadership was the independent variable, while positive school culture and school climate were the dependent variables. Descriptive statistics and simple linear regression were applied for analysis. The results show that adaptive leadership is significantly associated with both positive school culture and school climate, accounting for a meaningful proportion of the variance in each. Leadership practices characterized by responsiveness, participation, and flexibility contribute to favorable organizational conditions. However, the effect sizes suggest that leadership is only one of several influencing factors. The findings support adaptive leadership theory in vocational education and highlight the need for further research on additional organizational variables and longitudinal school improvement processes